CERITA RAKYAT AJISAKA SEBAGAI SUMBER IDE PERANCANGAN MOTIF BATIK TULIS UNTUK PAKAIAN - Maria Ghandes Sasmitha Angela; Darwoto (Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
The background of this product design is to create innovations in textile design, especially for written batik with the visualization of a folk tale entitled Ajisaka with the aim of conveying a message to the public to get to know this folklore better. This work will later explore the form of the Ajisaka folklore where the characters in the story are visualized into designs on written batik. The method used in this design consists of three stages, namely exploration, textile design process and textile embodiment. The first stage is to dig up information on various types of folklore in Indonesia, especially in Java. The second stage, describes the conceptual framework in the form of visual processing and color. The third stage, realizing the results of the design into a product that has use value. The results of this design process are (1) motifs from several narrations from folklore. (2) the combination used is the motif of pieces of narrative from the Ajisaka folklore as the main motif and floral motifs as supporting motifs. (3) produce a product in the form of adult women's clothing with an age range of 20-30 years. The design is intended as a means to introduce or revive folklore so that in the process of making written batik using appropriate colors and compositions so as to produce innovative products, using decorative figurative stylizations in making the motifs, in addition to that in its embodiment it uses primisima cloth media because the cloth is It has characteristics that easily absorb air so it will feel comfortable when worn.